Benefits of dietary polyphenols in Alzheimer’s disease - El Gaamouch, Farida; Chen, Fiona; Ho, Lap; Lin, Hsiao-Yun; Yuan, Chongzhen; Wong, Jean; Wang, Jun (Frontiers in Aging Neuroscience, 2022)
Alzheimer′s disease (AD) is an irreversible progressive neurodegenerative disease affecting approximately 50 million people worldwide. It is estimated to reach 152 million by the year 2050. AD is the fifth leading cause of death among Americans age 65 and older. In spite of the significant burden the disease imposes upon patients, their families, our society, and our healthcare system, there is currently no cure for AD. The existing approved therapies only temporarily alleviate some of the disease’s symptoms, but are unable to modulate the onset and/or progression of the disease. Our failure in developing a cure for AD is attributable, in part, to the multifactorial complexity underlying AD pathophysiology. Nonetheless, the lack of successful pharmacological approaches has led to the consideration of alternative strategies that may help delay the onset and progression of AD. There is increasing recognition that certain dietary and nutrition factors may play important roles in protecting against select key AD pathologies. Consistent with this, select nutraceuticals and phytochemical compounds have demonstrated anti-amyloidogenic, antioxidative, anti-inflammatory and neurotrophic properties and as such, could serve as lead candidates for further novel AD therapeutic developments. Here we summarize some of the more promising dietary phytochemicals, particularly polyphenols that have been shown to positively modulate some of the important AD pathogenesis aspects, such as reducing β-amyloid plaques and neurofibrillary tangles formation, AD-induced oxidative stress, neuroinflammation and synapse loss. We also discuss the recent development of potential contribution of gut microbiome in dietary polyphenol function.